Avoiding monocultures in the European Union: the case for the mutual recognition of difference in conditions of uncertainty - Richard Bronk; Wade Jacoby (London School of Economics and Political Science (LSE), European Institute, 2013)
The European Union is a unique blend of harmonised practice and mutual recognition of different regimes. In this paper, we conclude that arguments for continued diversity are more significant than the existing literature recognises. We build on the Varieties of Capitalism argument for trading on (rather than effacing) comparative institutional advantages, as well as Sabel and Zeitlin's for the learning potential of 'directly deliberative polyarchy'. We link these to the emphasis in non-EU focused literature on the lack of robustness implied by one-size fits all. Diversification of gene pool, model or policy regime is essential insurance against unforeseen threats. We also focus on dangers of epistemic closure implied by analytical monocultures in conditions of uncertainty, and on epistemological justifications for disciplined eclecticism in regulation and analysis. The relevance to banking and fiscal union and other policy areas is briefly considered, as are the dangers posed by an emerging German Consensus.
Keywords: 330; mutual recognition; policy diversity; analytical monocultures; German Consensus; uncertainty